Observation of multiple bulk bound states in the continuum modes in a photonic crystal cavity - Rui Chen; Yi Zheng; Xingyu Huang; Qiaoling Lin; Chaochao Ye; Meng Xiong; Martijn Wubs; Yungui Ma; Minhao Pu; Sanshui Xiao (Beilstein Journal of Nanotechnology, 2023)
Obtaining bound states in the continuum (BICs) in photonic crystals gives rise to the realization of resonances with high quality factors for lasing and nonlinear applications. For BIC cavities in finite-size photonic crystals, the bulk resonance band turns into discrete modes with different mode profiles and radiation patterns. Here, photonic-crystal BIC cavities encircled by the photonic bandgap of lateral heterostructures are designed. The mirror-like photonic bandgap exhibits strong side leakage suppression to confine the mode profile in the designed cavity. Multiple bulk quantized modes are observed both in simulation and experiment. After exciting the BIC cavity at different positions, different resonance peaks are observed. The physical origin of the dependence between the resonance peak and the illuminating position is explained by analyzing the mode profile distribution and further verified by numerical simulations. Our findings have potential applications regarding the mode selectivity in BIC devices to manipulate the lasing mode in photonic-crystal surface-emitting lasers or the radiation pattern in nonlinear optics.